Question
upstudy study bank question image url

Solve the following equation for the variable by first simplifying each side of the equation and applying the addition property. \( 7 a-3-6 a=-5+9 \) \( a=\square \)

Ask by Garrett Boone. in the United States
Feb 21,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

\( a = 7 \)

Solution

Step 1: Simplify each side of the equation. On the left side:  7a - 3 - 6a Combine like terms (7a - 6a):  a - 3 On the right side:  -5 + 9 Combine the constants:  4 Now the equation becomes:  a - 3 = 4 Step 2: Isolate a using the addition property. Add 3 to both sides of the equation:  a - 3 + 3 = 4 + 3  a = 7 Thus, a = □ becomes a = 7.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To simplify the equation \( 7a - 3 - 6a = -5 + 9 \), start by combining like terms on both sides. On the left side: \( 7a - 6a = 1a \) or just \( a \), and for constants: \( -3 \) stays the same. Thus, we have: \[ a - 3 = -5 + 9. \] Now simplify the right side: \[ -5 + 9 = 4. \] So the equation now is: \[ a - 3 = 4. \] Using the addition property, add 3 to both sides: \[ a - 3 + 3 = 4 + 3 \] \[ a = 7. \] Thus, the solution is: \( a = 7 \).

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy